Career Development as a Mediator of the Relationship Between Education Level, Competence, and Employee Performance - Luh Kartika Ningsih; Komang Trisna Suria Noviantini; A.A.N Eddy Supriyadinata Gorda; Ni Luh Putu Eka Yudi Prastiwi (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to determine the effect of education level and competence on employee performance with career development as an intervening variable at Perumda Air Minum Tirta Hita Buleleng. This study uses a quantitative approach, and the sample used is 77 employees. The sample collection method uses proportional random sampling techniques. Data collected used questionnaires. The data analysis technique used SEM PLS. The results showed that education level affected career development, competence affected career development, education level affected employee performance, competence affected employee performance, career development affected employee performance, education level affected employee performance through career development, and competence affected employee performance through career development at Perumda Air Minum Tirta Hita Buleleng